2004
DOI: 10.1902/jop.2004.75.3.408
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Menstrual Cycle on Periodontal Health

Abstract: We observed changes in gingival scores during the menstrual cycles of periodontally healthy women. These changes need to be addressed when analyzing data from epidemiological and treatment studies in premenopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
1
20

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(86 citation statements)
references
References 30 publications
3
62
1
20
Order By: Relevance
“…[17] Increased CAL in PCOS group is due to the hyperresponsive inflammatory process that is produced as a result of hormonal imbalance. These inflammatory processes play an imperative role in the progression of periodontal disease and subsequent increase in the gingival sulcus depth and bone loss.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[17] Increased CAL in PCOS group is due to the hyperresponsive inflammatory process that is produced as a result of hormonal imbalance. These inflammatory processes play an imperative role in the progression of periodontal disease and subsequent increase in the gingival sulcus depth and bone loss.…”
Section: Discussionmentioning
confidence: 99%
“…This was done to minimise the effects of hormonal changes during menstrual cycle. [14][15][16][17] The GI and CAL were calculated at four sites on each tooth. The GI was assessed after drying gingiva with cotton rolls.…”
Section: Periodontal Examinationmentioning
confidence: 99%
“…Nos últimos anos, alguns estudos (Armitage, 1999;Mariotti, 1999) Diversos estudos descritos na literatura avaliaram a influência dos hormônios sexuais sobre a resposta inflamatória dos tecidos periodontais marginais durante a puberdade, gestação, ciclo menstrual, pré-menopausa e com o uso de anticoncepcionais (Elattar, 1976;Kalkwarf, 1978;Miyagi, Morishita et al, 1993;Lapp, Thomas et al, 1995;Machtei, Mahler et al, 2004;Lapp e Lapp, 2005). Os resultados obtidos nestes estudos sugeriram que os níveis elevados de hormônios sexuais durante essas diferentes condições provocam aumento dos níveis de diversas citocinas inflamatórias, que estão associadas a alterações inflamatórias do tecido gengival, incluindo maior sangramento à sondagem (Kalkwarf, 1978;Brooks, 1980;Miyagi, Morishita et al, 1993;Amar e Chung, 1994;Lapp, Thomas et al, 1995;Machtei, Mahler et al, 2004;Lapp e Lapp, 2005).…”
Section: Discussionunclassified
“…Machtei et al (Machtei, Mahler et al, 2004) ao avaliarem as variações de saúde do periodonto marginal durante as diferentes fases do ciclo menstrual, observaram que ocorre aumento no índice gengival no período pré-menstrual e na fase da ovulação, em mulheres periodontalmente saudáveis. Cabe ressaltar que não foram observadas alterações estatisticamente significantes no índice de placa, recessão e nível de inserção, o que significa que o aumento no índice gengival não está relacionado com aumento na presença de placa bacteriana.…”
Section: Ação Dos Hormônios Sexuais Sobre Os Tecidos Periodontaisunclassified
“…It is reported that gingivitis affects 65-75% of pregnant women 55 . Moreover, women in ovulation and pre-menstruation phase are more prone to acquired periodontal diseases 56 . Ovulation induction by clomiphene citrate is able to induce gingival inflammation in women 57 .…”
Section: Gender As Risk Factor In Periodontal Diseasementioning
confidence: 99%